Interactive Teleconferencing Combining Spatial Audio Object Coding and DirAC Technology - Herre, Jürgen; Falch, Cornelia; Mahne, Dirk; Del Galdo, Giovanni; Kallinger, Markus; Thiergart, Oliver (128nd AES Convention, 2010)
The importance of telecommunication continues to grow in our everyday lives. An ambitious goal for developers is to provide a most natural way of audio communication by giving users the impression of being located next to each other. MPEG Spatial Audio Object Coding (SAOC) is a technology for coding, transmitting, and interactively reproducing spatial sound scenes on any conventional multi-loudspeaker setup (e.g. ITU 5.1). This paper describes how Directional Audio Coding (DirAC) can be used as a recording front-end for SAOC based teleconference systems to capture acoustic scenes and to extract the individual objects (talkers). By introducing a novel DirAC to SAOC parameter transcoder, a highly efficient way of combining both technologies is presented which enables interactive, object-based spatial teleconferencing.
herre_papers_spatial_audio_coding_and_3d_audio_coding